2014
DOI: 10.1007/s00284-014-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids Induce Tolerance to Zinc- and Copper-Exposed Fungi Under Various Growth Conditions

Abstract: Heavy metals, Zn and Cu, in high concentration (2 mM for Zn and 0.5 mM for Cu) have some inhibiting effect on the growth of Aspergillus niger and Penicillium citrinum. Toxic effects of these metals considerably depend on cultivation conditions including nitrogen sources, pH of nutrient media, and its consistency (presence or absence of agar). In general, nitrate media provides less inhibiting effect on fungal growth under heavy metal exposure than ammonium-containing media. Adding of Zn in nitrate media induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…On the other hand, when maize plants were exposed to 100 µm Cu or Cd in a hydroponic culture, significant secretion of citrate was not observed, in contrast to that observed in the presence of Al (Chaffai, Tekitek, and El Ferjani, 2006). It should be noted that the extracellular production of organic acids is considered an important mechanism in increasing heavy metal tolerance not only in higher terrestrial plants, but also in fungi (Sazanova et al, 2015) and in hydrophytes (Kurilenko and Osmolovskaya, 2015).…”
Section: Plant Sciencementioning
confidence: 86%
“…On the other hand, when maize plants were exposed to 100 µm Cu or Cd in a hydroponic culture, significant secretion of citrate was not observed, in contrast to that observed in the presence of Al (Chaffai, Tekitek, and El Ferjani, 2006). It should be noted that the extracellular production of organic acids is considered an important mechanism in increasing heavy metal tolerance not only in higher terrestrial plants, but also in fungi (Sazanova et al, 2015) and in hydrophytes (Kurilenko and Osmolovskaya, 2015).…”
Section: Plant Sciencementioning
confidence: 86%
“…Fungi (EPF included) are known to alter their environment by releasing organic acids [ 67 ], and the concentrations of nutrients such as Fe, Cu, and Ag [ 68 ], Zn [ 69 ] or P [ 70 ] increase as a result. The released organic acids lower the pH of the medium and increase the solubility of Fe oxides.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been supported previously in fungi and plants. More specifically, the toxic effect of Zn and Cu on Aspergillus niger and Penicillium citrinum growth has been reported to depend on physiological conditions related to nitrogen sources, and in particular, nitrate media provided reduced metal toxicity compared to ammonium‐containing media (Sazanova et al ., ). These findings are compatible with the idea that ammonium represses purine catabolism and leads to depletion of purine metabolites, which in turn leads to reduced metal resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have further shown that various abiotic stresses activate allantoin and allantoate accumulation, conferring increased stress resistance to plants (Yesbergenova et al ., , Alamillo et al ., , Watanabe et al ., , Irani and Todd, ). Finally, there are also reports that show that certain nucleobases (Rodgers and Armentrout, ; Brandi‐Blanco et al ., ) and other metabolites, such as oxalic acid (Sazanova et al ., ) or proline (Dinakar et al ., ) chelate metals. In one case, metal chelation has been further shown to contribute to metal tolerance in fungi (Sazanova et al ., ).…”
Section: Discussionmentioning
confidence: 99%